The need for financial incentives to promote agroforestry systems as biodiversity islands in degraded landscapes - Montagnini, Florencia (2025)
Agroforestry systems (AFS) are becoming more relevant due to their multiple roles in food sovereignty, restoration, biodiversity protection, and climate change adaptation and mitigation. Financial incentives are needed to promote them, especially for AFS whose design and management provide ecosystem services such as acting as “biodiversity islands” in altered landscapes. Voluntary biodiversity credits (VBC) are an alternative that we are examining for application in AFS with perennial species such as cacao, yerba mate and others for which there are standards that could be applied to access VBC.